Inhibitory non-invasive brain stimulation to homologous language regions as an adjunct to speech and language therapy in post-stroke aphasia: a meta-analysis - Otal, Begonya; Olma, Manuel C.; Flöel, Agnes; Wellwood, Ian (Frontiers in Human Neuroscience, 2015)
Chronic communication impairment is common after stroke, and conventional speech and language therapy (SLT) strategies have limited effectiveness in post-stroke aphasia. Neurorehabilitation with non-invasive brain stimulation techniques (NIBS) ‒ particularly repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS) ‒ may enhance the effects of SLT in selected patients. Applying inhibitory NIBS to specific homologous language regions may induce neural reorganization and reduce interhemispheric competition. This mini review highlights randomized controlled trials (RCTs) and randomized cross-over trials using low-frequency rTMS or cathodal tDCS over the non-lesioned non-language dominant hemisphere and performs an exploratory meta-analysis of those trials considered combinable. Using a random-effects model, a meta-analysis of nine eligible trials involving 215 participants showed a significant mean effect size of 0.51 (95% CI = 0.24 to 0.79) for the main outcome “accuracy of naming” in language assessment. No heterogeneity was observed (I2 = 0%). More multicenter RCTs with larger populations and homogenous intervention protocols are required to confirm these and the longer-term effects.